Current progress in sports genomics - Ahmetov, I. I.; Fedotovskaya, O. N. (Advances in Clinical Chemstry, 2015)
Understanding the genetic architecture of athletic performance is an important step in the development of methods for talent identification in sport. Research concerned with molecular predictors has highlighted a number of potentially important DNA polymorphisms contributing to predisposition to success in certain types of sport. This review summarizes the evidence and mechanistic insights on the associations between DNA polymorphisms and athletic performance. A literature search (period: 1997-2014) revealed that at least 120 genetic markers are linked to elite athlete status (77 endurance-related genetic markers and 43 power/strength-related genetic markers). Notably, 11 (9%) of these genetic markers (endurance markers: ACE I, ACTN3 577X, PPARA rs4253778 G, PPARGC1A Gly482; power/strength markers: ACE D, ACTN3 Arg577, AMPD1 Gln12, HIF1A 582Ser, MTHFR rs1801131 C, NOS3 rs2070744 T, PPARG 12Ala) have shown positive associations with athlete status in three or more studies, and six markers (CREM rs1531550 A, DMD rs939787 T, GALNT13 rs10196189 G, NFIA-AS1 rs1572312 C, RBFOX1 rs7191721 G, TSHR rs7144481 C) were identified after performing genome-wide association studies (GWAS) of African-American, Jamaican, Japanese, and Russian athletes. On the other hand, the significance of 29 (24%) markers was not replicated in at least one study. Future research including multicenter GWAS, whole-genome sequencing, epigenetic, transcriptomic, proteomic, and metabolomic profiling and performing meta-analyses in large cohorts of athletes is needed before these findings can be extended to practice in sport.